x+1x+9=23

Simple and best practice solution for x+1x+9=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+1x+9=23 equation:


Simplifying
x + 1x + 9 = 23

Reorder the terms:
9 + x + 1x = 23

Combine like terms: x + 1x = 2x
9 + 2x = 23

Solving
9 + 2x = 23

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 2x = 23 + -9

Combine like terms: 9 + -9 = 0
0 + 2x = 23 + -9
2x = 23 + -9

Combine like terms: 23 + -9 = 14
2x = 14

Divide each side by '2'.
x = 7

Simplifying
x = 7

See similar equations:

| .38=2b+25*(-7) | | 17x^17=0 | | (Y-3)(Y^2+BY+C)=Y^3-27 | | 19(3-v)+10v=-15 | | -4(6x-7)-3(4+2x)= | | 3x+45=3(x-3) | | 6X(2x-1)= | | 3(2x-y)+6y= | | 0.3(y+4)=0.4(y-2) | | 19=35+9x | | 2(-1)-4-y=12 | | 3y-(y+2x)+x= | | 6y-9-3y+8=0 | | 2(0)-4-y=12 | | 4y-5x=4 | | 2(1)-4-y=12 | | 2z-18-4z=-9 | | -7+u=3 | | y-53=294 | | X^2+6x+6.75=0 | | 4x+7x-3=0 | | -101=w+5.3 | | -0.8k-3.1=.5 | | 4(2x-1)-(3-1)=3 | | 9x^2+18x=22 | | 4(2x-1)-(3x-1)=3 | | x+2/4=27/12 | | F(x)=x*2-6x-15 | | 31=7c+-74 | | 15*15+9*9=x*x | | 4x+206=12+10 | | x-8+9-3=11 |

Equations solver categories